Graphene Q-switched 1.4 µm solid state laser. (23rd May 2018) - Han, Shuo; Zhou, Ying; Wang, Zhengping; Hu, Dawei; Xu, Xiaodong; Yu, Haohai; Xu, Jun; Xu, Xinguang
Abstract: An LD pumped Nd:LuGdAG (Nd:Lu2.9 Gd0.1 Al5 O12 ) eye-safe laser is reported in this paper for the first time. Using a plano-concave resonator, maximum continuous wave output powers of 1.00 and 1.05 W were obtained under an absorbed pump power of 8.52 W for T = 2%–3% and 5%–7%, corresponding to an optical to optical conversion efficiency of 12.3% and 11.7% and a slope efficiency of 14.5% and 13.6%. With five to seven layers of graphene saturable absorber, passively Q -switched 1444 nm operation was achieved for the first time. The maximum average output power found was 0.29 W with 324 ns as the shortest pulse width and a highest repetition rate of 64 kHz.